2017
DOI: 10.5465/amj.2014.0767
|View full text |Cite
|
Sign up to set email alerts
|

Green by Comparison: Deviant and Normative Transmutations of Job Search Envy in a Temporal Context

Abstract: We propose a novel temporal-based theory of how a painful social comparative emotion-job search envy-transmutes as deviant or normative job search behaviors (resume fraud or search effort). We theorize that as job searches progress across time or discrete events, temporal-based pressure increases via perceptions that situations are less changeable or more critical, propelling envious job seekers toward deviant rather than normative search behavior. We propose that market-based pressure, deriving from employmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 75 publications
(131 reference statements)
0
54
0
Order By: Relevance
“…Furthermore, internships provide preparation in job acquisition skills, such as networking, résumé writing, and conducting job interviews (Gault et al, ). Similar to job seekers who are looking for a job, students typically have to search for an adequate internship themselves (Dineen, Duffy, Henle, & Lee, ). However, not much is known about how students can best conduct this search and what search processes lead to the best possible outcomes (DeRue, Nahrgang, Hollenbeck, & Workman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, internships provide preparation in job acquisition skills, such as networking, résumé writing, and conducting job interviews (Gault et al, ). Similar to job seekers who are looking for a job, students typically have to search for an adequate internship themselves (Dineen, Duffy, Henle, & Lee, ). However, not much is known about how students can best conduct this search and what search processes lead to the best possible outcomes (DeRue, Nahrgang, Hollenbeck, & Workman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study seeks to make two major contributions to the organizational literature. First, we take a distinct departure from the focus on enviers as in the majority of research (e.g., Cohen‐Charach & Mueller, ; Dineen, Duffy, Henle, & Lee, ; Duffy et al., ; Schaubroeck & Lam, ; Tai et al., ) and examine an important range of implications associated with being envied from targets’ perspectives (Foster, ; Vecchio, , ). Envy “involves interactions and relationships”, and, therefore, the experience of being envied is also common in organizations (Parrott, , p. 455).…”
mentioning
confidence: 99%
“…We broadly define workplace success because "the reasons for being envied are nearly limitless" (Parrott, 2016, p. 455), and success can be construed in a multitude of ways depending on the perceiver (e.g., exceptional customer interaction skills, relationship with supervisor, leadership capabilities, better assignment). Aligned with research demonstrating that individuals typically envy more than one colleague (e.g., Dineen et al, 2017;Duffy et al, 2012;Vecchio, 1995Vecchio, , 2000Vecchio, , 2005Vecchio, , 2007, we study the perceptions of being generally envied by multiple coworkers and its varying implications for work engagement and performance.…”
mentioning
confidence: 99%
“…According to Cohen-Charash & Mueller (2007) and Vecchio (2007), malicious envy can eventually enhance extreme levels of aggression towards the envied parties and this can even lead to the envious person sabotaging the envied party. Other precedent studies (Cohen-Charash & Mueller, 2007;Dineen et al, 2017;Smith & Kim, 2007;van de Ven et al, 2009) revealed that instead of increasing focus on selfimprovement, envious people trapped within malicious envy believe they do not have the ability to accomplish or reach the standards of their target. Thus, instead of self-improvement, they focus on plotting attempts that could tarnish the envied person's image, accolades, and life.…”
Section: Discussionmentioning
confidence: 99%
“…Within an organization, employees actively compare their skills with their colleague's in an upward social way (Brown et al, 2007). A few research studies raised the question of whether envy can be an impetus for advancement (Cohen-Charash, 2009;Dineen et al, 2017;Lange & Crusius, 2015;Schaubroeck & Lam, 2004). As expected, an initial corroboration points out that envy ultimately plays a pivotal role in amplifying an employee's success, as operationalized by job performance (Barrick et al, 2002;Ferris et al, 2013).…”
Section: Social Comparison Envy Perceived Organizational Support Anmentioning
confidence: 91%